Costs in the Norwegian Payment System - Olaf Gresvik; Harald Haare (Norges Bank, 2009)
We calculate social and private cost for the use and production of payment services in Norway for 2007. The calculations include banks', merchants' and households' cost for cash, cards and giro payments. The social cost is calculated to be 0.49 % of GDP, or NOK 11.16 billion. Costs are also calculated on a per-service basis. The results are compared with data from earlier cost surveys by Norges Bank. The unit costs of the most popular services have decreased over the years. Efficiency and productivity of banks' payment service operations has improved. We also make comparisons between frameworks, methodologies, and results from cost surveys in five European countries.
hdl:11250/2507918
Keywords: D12; D23; D24; 330; cash payments; card payments; giro payments; social costs; private costs; unit costs; banks' efficiency